Fumaderm® in daily practice for psoriasis: dosing, efficacy and quality of life. (1st October 2014) - Walker, F.; Adamczyk, A.; Kellerer, C.; Belge, K.; Brück, J.; Berner, T.; Merten, K.; Núnez Gómez, N.; Neureither, M.; Röcken, M.; Ghoreschi, K.; ,
Summary: Background: Patients with psoriasis suffer from chronic skin disease and impaired quality of life. With a prevalence of 1–3% of the population, psoriasis is one of the most common chronic inflammatory autoimmune diseases. Fumaric acid esters (Fumaderm ® ) are approved for the treatment of psoriasis in Germany, but regular Fumaderm therapy with six tablets per day is often limited due to adverse events. Objectives: This observational study recorded data on quality of life, treatment efficacy and drug dosing in patients suffering from psoriasis treated with Fumaderm under conditions of daily practice in 78 dermatological centres. Patients and methods: In this prospective, multicentre, noninterventional trial we included adult patients with severe plaque psoriasis under outpatient conditions receiving Fumaderm according to the current summary of product characteristics for systemic treatment of psoriasis. At baseline and after 3, 6 and 12 months the dosing regimen under daily conditions, Dermatology Life Quality Index (DLQI) and clinical efficacy with the Psoriasis Area and Severity Index (PASI) were documented. Results: A total of 249 patients were included. The mean DLQI score at study entry was 9·95; the mean PASI was 16·8. The average treatment dose of Fumaderm was 2·8 tablets daily. More than 70% of patients were treated with one to three tablets daily and < 30% were treated with a dose ranging from four to six tablets daily. DLQI and PASI improved in the entire study population by 67·2% and 66·6%, respectively. Specifically, when analysing patients who started Fumaderm within 4 weeks before baseline the mean DLQI score decreased from 11·8 to 2·9 (75% reduction) and the mean PASI score from 19·84 to 7·35 after 12 months (63% improvement). Conclusions: This is the first field study analysing the use of Fumaderm and the improvement of quality of life in patients with psoriasis under daily outpatient conditions. The improvement of DLQI obtained with Fumaderm was comparable with the improvement observed in patients with psoriasis treated with modern biologics. Importantly, in most patients with good clinical response, the treatment dose was one to three tablets daily. Abstract : What's already known about this topic? Patients with psoriasis suffer from chronic skin disease and impaired quality of life. Fumaric acid esters (Fumaderm ® ) are approved for the treatment of psoriasis in Germany. Regular Fumaderm ® therapy with six tablets per day is often limited due to adverse events. What does this study add? This is the first report demonstrating improvement of quality of life in patients with psoriasis treated with Fumaderm ® under daily outpatient conditions. The improvement in Dermatology Life Quality Index obtained with Fumaderm ® was comparable to the improvement observed in patients with psoriasis treated with modern biologics. Good clinical response was observed in patients treated with even a low to medium dose of Fumaderm ® (one to three tablets daily).